Culinary tourism as a post disaster recovery marketing tool for sri lanka tourism promotion: A study of south coast of sri lanka - Perera, L.A.P.C.; Wijesundara, W.G.S.R. (University of Jaffna, 2020)
Culinary Tourism has been grown exponentially every year as it attracts thousands of tourists by arousing their taste buds towards food. Hence, Culinary Tourism has been already considered as a motive for the choice of travel destinations. The tourism industry is highly susceptible to disasters collapsing entire industry in one second. This brings a challenge for replenishing the tourism industry after a disaster. However, Food or culinary makes a destination unique and therefore, gastronomic tourism is perceived nowadays as one of the significant commitments for strengthening or consolidating specific tourist destinations. Thus, gastronomy is a strategic element as a post-disaster marketing tool for promoting tourists’ destinations. Therefore, current research aims to delineate whether culinary tourism can be used as a post disaster recovery marketing tool for promoting tourism in Sri Lanka and identifying the most influential variable as a post disaster recovery marketing tool for the promotion of tourism in Sri Lanka. A self-administered questionnaire-based survey was conducted around South Coast of Sri Lanka with 100 tourists by using a purposive sampling technique. A comprehensive literature review was done and Multiple Regression Analysis was used to analyze the data to achieve the study's objectives. SPSS 20 software was used as the analytical tool for the study. The results revealed that culinary tourism as a post-disaster marketing tool has a significant and direct impact on tourism promotion in Sri Lanka. To recover Sri Lankan Tourism industry using culinary tourism as a post-disaster recovery marketing tool to a satisfactory level, food consumption patterns of culinary tourists should be properly diagnosticated and the destination environments should be restructured surprisingly and destination foods needs its signature. The results of this study suggest strongly that advertisements and publicity campaigns that use celebrity endorsements may have the best chance of persuading visitors to return to a destination following a disastrous event. Further, studies related to culinary tourism with the mediation effect of integrated destination management can be consummated.
Keywords: Culinary tourism; Gastronomy; Integrated destination management and post-disaster recovery marketing tool